A Critique on the Book Science, Society, Development: Papers on Public Understanding from both Historical and Philosophical Perspectives - Mohammad Samiei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Public understanding, an important subject that is less discussed in the available literature, is under scrutiny by the book entitled Science, Society, Development: Papers on Public Understanding from both Historical and Philosophical Perspectives. Using critical rationalism as its main analytical approach, the book attempts to make a correction on the notion of science in the public perspective and also about the definition and necessity of public understanding. Despite the success of critical rationalism in enlightening the public about science, this approach alone is unable in clarifying non-scientific motivations such as political and economic interests behind propagating science. To prevent this shortcoming, we could consider besides critical rationalism some other approaches which help us and the public detect non-scientific motivations and to distinguish between genuine attempts and those who look at science as a means. This paper also discusses some formative points and suggests four complementary additions to the book. Overall, the book is an in-depth and valuable attempt on this subject.